PENENTUAN NILAI KONTRAK OPSI SAHAM TIPE EROPA MENGGUNAKAN MODEL CONSTANT ELASTICITY OF VARIANCE - MAGOL, LUSIA EMITRIANA; DHARMAWAN, KOMANG; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika, 2020)
Investment is a very sensitive matter especially relating to securities commonly known as shares. Shares are not merely as securities or certificates of ownership but as a business area in achieving profits. One alternative factor for investment is option. Stock options are one of the trading tools used to secure stock investments owned by investors. The real value of stock options can be known when the due date. The stock option value formula can be used to find out the value before the due date. The most widely known stock option value is to use the Black-Scholes equation which is obtained from a constant volatility value. Then it was developed because it saw the conditions in the market based on the volatility of the value (not constant). The purpose of this study is to determine the value of stock options in the market based on volatile values ??that change using the Constant Elasticity of Variance model with the limit of European stock purchase options. If the resulting stock option value is greater than the option price in the market, investors are advised to buy the stock option .